A new species of Sternitta Fibiger, 2011 (Lepidoptera, Erebidae, Hypenodinae, Micronoctuini) from Cambodia - Qi, Mujie; Bae, Yangseop; Han, Huilin (Zootaxa, 2020)
Fibiger (2011) established the genus Sternitta in the Micronoctuidae, with Sternitta gregerseni Fibiger, 2011 from Nepal as the type species. The Micronoctuidae are currently treated as a tribe (Micronoctuini) within the Hypenodinae, and include over 400 described species. To date, the genus Sternitta (Micronoctuini: Micronoctuina) consists of seven species: S. goateri Fibiger, 2011 in Afghanistan; S. hackeri Fibiger, 2011 and S. gabori Fibiger, 2011 in Pakistan; S. parasuffuscalis Fibiger, 2011, S. suffuscalis (Swinhoe, 1886), S. gabori Fibiger, 2011 and S. magna Fibiger, 2011 in India; S. suffuscalis (Swinhoe, 1886) in Sri Lanka and S. gregerseni Fibiger, 2011 only in Nepal (Swinhoe 1886; Fibiger 2011). The genus Sternitta was considered by Fibiger to be among the more primitive micronoctuine genera, and it can be recognized by the sclerotized 8th abdominal sternite with prominent dorsal and ventral processes and, in the male genitalia of most species, by the divided ampulla into dorsal and ventral plates and by the dorsal spinelike processes on the anellus. In the present paper, the new species Sternitta mondulkiriensis sp. n. is described from Cambodia with habitus and male genitalia illustrated and compared with those of S. suffuscalis (Swinhoe, 1886). An updated checklist and a key to all the species are included.